Evaluation of a Novel Point-of-Care Lateral Flow Assay To Detect Cryptococcal Antigen in Plasma and CSF - Rolfes, Melissa; Butler, Elissa; Nabeta, Henry; Kwizera, Richard; Meya, David; Boulware, David (Opportunistic Infections, 2012)
Current diagnostics for Cryptococcal meningitis (CM) rely on India ink, CSF culture, or cryptococcal antigen (CRAG) latex agglutination test. India ink is relatively insensitive. Culture and CRAG require lab infrastructure. Recently, a novel point-of-care lateral flow assay (LFA) has been FDA-approved for diagnosis of C. neoformans in serum samples. The aim of this study was to evaluate the LFA performance in plasma and CSF samples. ART-naïve subjects with and without cryptococcosis were enrolled in two prospective cohorts in Kampala, Uganda. Initial CM diagnosis was by CRAG, India ink, and quantitative CSF culture. Plasma and CSF were frozen at - 80C. Quantitative CRAG titers and LFA testing with titers were conducted on stored CSF, plasma, and serum. Plasma samples were tested in 112 subjects (n=61 with CM, n=51 with no clinical OI). CSF was tested in 161 subjects with suspected meningitis (105 with CM) from 2006-2009 and on 102 (58 with CM) in 2011. LFA results were compared for concordance with CRAG latex agglutination, India ink, and CSF culture.The LFA was highly sensitive and specific with CSF and plasma samples compared to both culture and CRAG. CRAG and LFA assays had high Kappa concordance in plasma and CSF samples, 0.93 and 0.91, respectively. LFA titers were 2.5 – 10-fold higher than CRAG titers in CSF and in plasma, respectively; however high correlation existed between the two assays (Spearman’s ρ=0.90 for plasma and 0.93 for CSF; p<0.001 for each). Culture and India ink had much lower concordance (Kappa 0.69 and 0.72, respectively) with LFA results (due to better LFA sensitivity), and titers were less correlated with quantitative culture results (ρ=0.71, p<0.001). Similar low concordance with culture and India ink were also seen with CRAG titers; suggesting the LFA results were not false-positives but more sensitive in detecting cryptococcal infection. The LFA assay has excellent concordance with CRAG latex agglutination and titers in both plasma and CSF samples and is more sensitive than standard India ink and CSF culture. Because of the wide availability of plasma samples for other clinical assessments (e.g. CD4 testing), the excellent agreement with the established CRAG assay, and the ease of use, the cryptococcal LFA holds great promise for rapid diagnosis of CM as well as the potential for cryptococcal screening prior to ART initiation, particularly in resource-limited areas.